1986
DOI: 10.1103/physrevd.33.2253
|View full text |Cite
|
Sign up to set email alerts
|

Unsharp reality and joint measurements for spin observables

Abstract: The Einstein-Podolsky-Rosen (EPR) reality criterion is generalized to fit with the notion of positive-operator-valued observable occumng in quantum optics, stochastic quantum mechanics, and other fields of quantum physics. The resulting concept of unsharp reality for quantum systems is illustrated within stochastic spin space where it leads to a notion of unsharp spin property. Finally we investigate the possibility of joint spin measurements and give a brief discussion of the EPR-Bell argument for unsharp spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
340
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(349 citation statements)
references
References 19 publications
9
340
0
Order By: Relevance
“…It has been shown [15] that if tr[ρE] ≥ 1 − ε, then φ E L does not decrease this probability and the state change, measured by the trace-norm distance, is small to the order of √ ε. This demonstrates the stability of the EPR reality criterion against small deviations from actualization, and one may say that approximately real properties can be ascertained almost with certainty and without significantly altering the system.…”
Section: 4mentioning
confidence: 99%
“…It has been shown [15] that if tr[ρE] ≥ 1 − ε, then φ E L does not decrease this probability and the state change, measured by the trace-norm distance, is small to the order of √ ε. This demonstrates the stability of the EPR reality criterion against small deviations from actualization, and one may say that approximately real properties can be ascertained almost with certainty and without significantly altering the system.…”
Section: 4mentioning
confidence: 99%
“…But in the more general framework, it has been shown that certain complementary observables (in standard measurement) can be measured jointly if they are represented by a particular form of POVM (having an interpretation in terms of unsharpness) instead of being represented by projection operators [5,6]. Joint measurement of spin observables in different directions has been extensively studied by P. Busch [7]. He, by exploiting the necessary and sufficient condition for co-existence of two effects as given by Kraus [5], showed that a pair of unsharp spin properties E λ 1 (α 1 )and E λ 2 (α 2 )are co-existent (i.e.…”
Section: Existence Of Joint Measurement In Quantum Mechanicsmentioning
confidence: 99%
“…In the case of spin-1/2 particles, P. Busch [7,8] had first introduced collection of positive operators with the above said properties in a particular form which can be interpreted as unsharp spin observables. This particular unsharp observables are represented in the following form :…”
Section: Quantum Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Pairs of unsharp observables of the form (26) are probabilistically complementary but in general not complementary. We may derive a simple geometric criterion for the coexistence of such observables.…”
Section: Proposition Noncoexistent Observables Do Not Admit Any Jmentioning
confidence: 99%